Постоперативна хемоирадијација со единичен целен волумен, наспроти хемоирадијација со намалување на целниот волумен во третман на малигните глиоми - Стојковски, Игор (Медицински факултет, УКИМ, Скопје, 2018)
Malignant gliomas are the most common primary tumors of the brain with an incidence of about 3-4 new cases per 100 000 population. In Republic of Macedonia it is estimated that annually 219 new brain tumor cases will be diagnosed (primary and secondary), and it is assumed that about 80 will be malignant gliomas. Primary treatment of malignant gliomas is surgery, followed by radiotherapy in combination with chemotherapy. Postoperative radiotherapy combined with chemotherapy can increase the survival of patients with malignant gliomas twofold compared to surgery only. Total of 90 patients with previously surgically extirpated, histologically-verified malignant gliomas, were enrolled in this study from February 2014 to March 2016. Patients were randomized into 2 treatment groups. In the first group of patients (47 in total), radiation therapy was performed with a single radiation volume during the entire treatment, while in the second group (43 patients) a cone-down reduction of radiation volume has been performed during the last 8 fractions of radiation therapy. The prescribed radiation dose and chemotherapy in both groups of patients were identical: 60 Gy total tumor dose with 2 Gy dose per fraction, total of 30 fractions competitively with Temozolomide chemotherapy 75 mg/m2 every day for 42 days followed by adjuvant chemotherapy with 150 mg/m2 Temozolomide for 5 consecutive days with a 23 day break. The cycle was repeated every 28 days until reaching a maximum of 12 cycles of chemotherapy. The response from the therapy was followed with magnetic resonance imaging, which has been performed every three months, counting from the last radiation session. The extent of response was evaluated according to RANO criteria. Progression free survival and overall survival in patients in both groups were analyzed according to the Kaplan-Meir method. A comparison of the survival curves was made with the Log-rank test. Multivariate analysis tested the independence of those prognostic factors whose significance was determined by univariate analysis. Multivariate analysis was performed with the Cox regression model. The value of p < 0,05 was taken for significance value. Comparison of the one-year disease free survival and overall survival of patients treated in both groups, found no statistically significant difference, p=0,4745 and p=0,6199 respectively. Univariate analysis as significant prognostic factors for survival without progression of disease identified following variables: age (p=0,0029), tumor grade (p=0,0033) and the number of realized adjuvant chemotherapy cycles (p<0,0001). With univariate analysis, significant prognostic factors for total survival were following: age (p=0,0080), performance status according to ECOG (p=0,0262), mental score (p = 0,0381), tumor grade (p=0,0094), the number of realized chemotherapy cycles (p<0,0001) and the level of serum albumin before the start of radiotherapy (p=0,0423). Cox's multivariate analysis of the prognostic factors of survival without progression of the disease identified as independent significant beneficial prognostic factors: tumor grade III (p=0,0034) and number of realized adjuvant chemotherapy cycles equal or greater than six (p<0,0001). Multivariate analysis as independent significant favorable prognostic factors for total survival were: the age of patients less than or equal to 60 years (p = 0,0436), tumor grade III (p = 0,0191) and the number of realized adjuvant chemotherapy cycles equal or greater than six (p<0,0001). Based on this data it can be concluded that there was no difference in disease free survival and overall survival among patients in both treatment groups, which means that the outcome of patients with malignant gliomas who were treated with chemoiradiation did not depend on the size of the target volume, and therefore did not depend on whether radiotherapy was performed using only one volume or was carried out using a cone-down reduction in volume. Additional analysis of prognostic factors, as independent prognostic factors for disease free survival, highlighted tumor grade and the number of realized cycles of adjuvant chemotherapy, while as independent prognostic factors for overall survival were highlighted the age of patients, tumor grade and number of realized cycles of adjuvant chemotherapy. Prolongation of adjuvant chemotherapy with more than 6 cycles can be considered to be a safe procedure that is associated with minimal toxic effects and can also have a positive impact on disease free survival and on overall survival.
Postoperative chemoiradiation with a single target volume versus chemoiradiation with decreasing of the target volume in the treatment of malignant gliomas
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Снежана Смичкоска.
Keywords: malignant gliomas, postoperative radiotherapy, chemotherapy